The Novel ASIC2 Locus Is Associated with Severe Gingival Inflammation. (July 2016) - Zhang, S.; Divaris, K.; Moss, K.; Yu, N.; Barros, S.; Marchesan, J.; Morelli, T.; Agler, C.; Kim, S.J.; Wu, D.; North, K.E.; Beck, J.; et al.
An increasing body of evidence suggests a significant genetic regulation of inflammatory response mechanisms; however, little is known regarding the genetic determinants of severe gingival inflammation (GI). We conducted a genome-wide association study of severe GI among 4, 077 European American adults, participants in the Dental Atherosclerosis Risk in Communities cohort. The severe GI trait was defined dichotomously with the 90th percentile of gingival index ≥2 extent score. Genotyping was performed with the Affymetrix 6.0 array platform, and an imputed set of 2.5 million markers, based on HapMap Phase II CEU build 36, was interrogated. Genetic models were based on logistic regression and controlled for ancestry (10 principal components), sex, age, and examination center. One locus on chromosome 17 met genome-wide statistical significance criteria—lead single-nucleotide polymorphism: rs11652874 (minor allele frequency = 0.06, intronic to ASIC2 [acid-sensing ionic channel 2, formerly named ACCN1 ]; odds ratio = 2.1, 95% confidence interval = 1.6 to 2.7, P = 3.9 × 10 -8 ). This association persisted among subjects with severe periodontitis and was robust to adjustment for microbial plaque index. Moreover, the minor (G) allele was associated with higher levels of severe GI in stratified analyses among subsets of participants with high load of either "red" or "orange" complex pathogens, although this association was not statistically significant. While these results will require replication in independent samples and confirmation by mechanistic studies, this locus appears as a promising candidate for severe GI. Our findings suggest that genetic variation in ASIC2 is significantly associated with severe GI and that the association is plaque independent. Knowledge Transfer Statement: Persistent gingival inflammation reflected by bleeding usually precedes ongoing attachment loss or periodontal disease progression. Our findings suggest that genetic variation in ASIC2 that is associated with severe gingival inflammation might be used as a genetic marker to identify people at higher risk for periodontal disease. Ongoing studies to uncover the mechanistic link between ASIC2 and gingival inflammation could lead to novel therapeutic interventions.